Factors That Cause Audit Report Lag For Issuers In The Energy Sector On The Idx For The Period Of 2021 To 2023 - Juan Carlos Pangestu; Pamella Octavia (International Journal of Multidisciplinary Sciences and Arts, 2025)
The Audit Report Lag is a concern for stakeholders in decision-making, whether it is investing, selling shares, making acquisitions, and determining other policies. Audited financial statements are important in decision-making because they describe the financial activities and performance of the company. This study aims to examine the factors that cause Audit Report Lag in Energy Sector Companies at the IDX for the 2021-2023 Period. The results show that only the audit committee size variable has a significant negative effect on Audit Report Lag. Other variables do not have a significant effect on Audit Report Lag. The Sig F value is 0.047 <0.05 so it can be concluded that simultaneously there is a significant influence of the independent variables on financial distress. Further research is recommended to use non-financial variables such as Good Corporate Governance or environmental variables.